Effect of Low Atmospheric Pressure on Bubble Stability of Air-Entrained Concrete - Xuefeng Li; Pengyu Yang (Advances in Civil Engineering)
The effect of low atmospheric pressure of the environment on the air content and bubble stability of air-entrained concrete was investigated in Beijing and Lhasa. The results indicate that the reduction of atmospheric pressure can weaken the air-entraining capability of air-entraining agents (AEAs). The air content of fresh concrete decreased by 9%–39% when the atmospheric pressure dropped to 64 kPa. The bubble stability of concrete mixed at a low atmospheric pressure becomes worse. Within 50–55 min after mixing, the air content of concrete mixed at a low atmospheric pressure decreases greatly, and the void spacing factor increases obviously. The concrete mixed at a low atmospheric pressure will lose more air content when vibration time increases, leading to the decrease of air content and the increase of the spacing factor, which are more significant than the concrete mixed at normal atmospheric pressure. On the basis of the experiment results in this study, the type of AEAs must be carefully selected, and the vibration time must be strictly controlled to ensure that the air content of concrete will meet the design requirements in low atmospheric pressure areas.